Web services and formal methods 7th International Workshop, WS-FM 2010, Hoboken, NJ, USA, September 16-17, 2010: revised selected papers - WS-FM (Workshop) Hoboken, N.J.) 2010; Bravetti, Mario; Bultan, Tevfik; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the 7th International Workshop on Web Services and Formal Methods, WS-FM 2010, held in Hoboken, NJ, USA, in September 2010. The 11 revised full papers presented together with one invited paper were carefully reviewed and selected from 26 submissions. The papers feature topics such as web services; service oriented computing;  cloud computing; formal methods; verification specification; testing; and business process management.
Electronic reproduction.
Keywords: Web services -- Congresses; Formal methods (Computer science) -- Congresses; Electronic books